FORMATION OF PROFESSIONAL AND PEDAGOGICAL FUTURE TEACHER ORIENTATIONS AS FUNDAMENTALS HIS PEDAGOGICAL CULTURE (Pedagogy of Higher and Secondary Education, 2022)
The author in the article determines the result of research on the problem of professional and pedagogically-oriented forming as basic part of teacher’s culture.
Keywords: 1